2018
DOI: 10.3390/app8040540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Frequency on Microstructures, Mechanical and Corrosion Properties of AA6061 Joints

Abstract: Three thermal frequencies that were designated as 3, 4, and 5 Hz were used to reveal the microstructural evolution, mechanical, and corrosion properties of AA6061-T6 sheets that were welded by double pulsed gas metal arc welding (DP-GMAW) using microstructural observations, microhardness tests, tensile tests, bend tests, impact tests, and corrosion tests. A self-developed welding system consisted of a digital multifunctional welder and an arc dynamic waveform wavelet analyzer was chosen to perform welding oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Strong and weak pulse trains are continuously alternated during this process, which forces gases formed by the welding processes out of the weld. Therefore, double-pulse MIG welding reduces the effects of weld pores, reduces the sensitivity of the joint to cracks, and improves the finish and mechanical properties of the weld [18].…”
Section: Design Of Current Waveform Parameters For Double-pulse Mig Wmentioning
confidence: 99%
“…Strong and weak pulse trains are continuously alternated during this process, which forces gases formed by the welding processes out of the weld. Therefore, double-pulse MIG welding reduces the effects of weld pores, reduces the sensitivity of the joint to cracks, and improves the finish and mechanical properties of the weld [18].…”
Section: Design Of Current Waveform Parameters For Double-pulse Mig Wmentioning
confidence: 99%
“…Xue et al [17] used the RSM combined with the grey wolf algorithm to optimize the process parameters and improve the weld profile and performance. In summary, optimizing welding process parameters using RSM is already common, but there is still a lack of optimization for DP-GMAW process parameters [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [18] introduced a dual-wire DP-GMAW with a median current waveform based on the conventional rectangular pulse and found that changed the median current, the average welding current also changed. The research on increasing the stirring effect of the molten pool mainly includes low-frequency [19, 20], current amplitude [21], and additional technology [22]. Liu et al [23] observed the change of the molten pool profile during the DP-GMAW welding process and found that the molten pool profile changes periodically with the change of low-frequency.…”
Section: Introductionmentioning
confidence: 99%